Sorghum's saviour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
World-wide about 58 million tonnes of sorghum are produced each year, on 44 million hectares of land. However one fungal infestation has the ability to wipe out entire crops of sorghum, as well as devastating other cereal crops. The disease ergot,...